SENSITIVITAS METODE PENDETEKSIAN DIFFERENTIAL ITEM FUNCTIONING (DIF) - SUDARYONO SUDARYONO (Jurnal Evaluasi Pendidikan, 2012)
The prime objective of this study is to find out the empirical data about a comparison sensitivity as Scheuneman’s Chi-square, Mantel-Haenszel methods and Item Response Theory (IRT) Rasch model in Differential Item Functioning (DIF) detection. The study used experimental methods with 1 x 3 design. The independent variables were, Scheuneman’s Chi-Square methods, Mantel-Haenszel methods and IRT Rasch model. This specific research aims at revealing: (1) the characteristics of test items based on the of classical test-theory, (2) the standard error measurement of classical test theory, and (3) the items detected as containing Differential Item Functioning (DIF) based on gender. Analysis of this study was based on testee’s response to the Mathematics test in the National Examination at Senior High School in Tangerang, 2008/2009 academic year. The data source was computer answer sheets of 5000 consist of 2500 from male student responses and 2500 female student responses, established using the simple random sampling technique. A result of the descriptive analysis using the classical test theory indicated that 28 out of 40 mathematics test items were good, with a reliability index of 0,827. The results indicated that all methods were good for the detection of DIF, but IRT Rasch model was the most sensitive among those methods compared with Mantel-Haenszel, and Sceuneman’s chi-square methods. The result of DIF analysis on the mathematics test was find any items containing DIF based on gender differences.